Diagnosis, Prevention, and Control of Hypertension in Iran: A SWOT Analysis - Masoumeh Gholizadeh; Ali Janati; Rahim Khodayari -Zarnaq; Mohammad Zakaria Pezeshki; Fateme Arabi Basharic; Noora rafiee (Health Technology Assessment in Action, 2023)
Abstract Background: Hypertension is one of the most important risk factors of cardiovascular morbidity and mortality that holds a unique place in population health and health care. Objectives: Given the exponential rise of high blood pressure as one of the major health problems, this study aimed to investigate the current situation and provide a strengths, weaknesses, opportunities, and threats (SWOT) analysis in the management of hypertension. Methods: A qualitative study of 12 interviews was conducted with policymakers and managers. The sampling method was purposive sampling. Data collection was performed from January to July 2020. A thematic approach was used to analyze the data. The consolidated criteria for reporting qualitative research 32-item (COREQ-32) checklist was applied to ensure quality control in the study design, analysis, and data reporting. Results: A total of 12 factors were identified as SWOT. The most important strengths included universal coverage of health services, provision of team-based care, and self-care training. The weaknesses were related to the therapeutic approach, long-term planning, and continuity of programs. Cooperation of other sectors with the health system and the existence of health management training centers were noted as opportunities to better implement hypertension management programs and confront threats such as conflicts of interest between guilds and organizations and crises. Conclusions: High blood pressure can be prevented. The present direction toward health-oriented policies can be changed in all sectors by taking advantage of the existing strengths and opportunities.